Fluorophore Release from a Polymethinic Photoremovable Protecting Group Through a Nonlinear Optical Process. Issue 9 (12th September 2017) - Rodríguez‐Romero, Jesús; Guarin, Cesar A.; Arroyo‐Pieck, Andres; Gutiérrez‐Arzaluz, Luis; López‐Arteaga, Rafael; Cortés‐Guzmán, Fernando; Navarro, Pedro; Peon, Jorge
Abstract: The front cover artwork is provided by members of the Instituto de Química at Universidad Nacional Autónoma de México (UNAM). The image represents a spatially localized photochemical cleavage induced by two‐photon absorption of NIR ultrashort laser pulses. A highly fluorescent species is formed in the process. Read the full text of the Article at10.1002/cptc.201700076 . Abstract : "A novel molecular photoactivation scheme is presented. It consists of a cyanine dye acting both as a two‐photon absorber and a photo‐removable protecting group. A highly fluorescent anthracenic chromophore is formed after the nonlinear optical process…" This and more about the story behind the front cover can be found in the Article at10.1002/cptc.201700076 .